The state of CAD 2017 : reinventing design and manufacturing - Barlow, Mike (O'Reilly Media, 2017)
The traditional manufacturing process for moving an idea from initial concept to finished product consists of several stages, each involving a different set of specialists. But not any longer. With this report, you'll learn how today's cloud-based computer-aided design (CAD) systems can unify multiple stages into a relatively seamless end-to-end process that reduces the product development cycle from years to weeks. Author Mike Barlow examines this new manufacturing paradigm through interviews with cloud-based CAD vendors, including Autodesk, Onshape, and PTC. You'll also learn how specialty product manufacturers use new CAD systems for quick prototyping, iteration, and closer communication and collaboration among design, engineering, assembly, and manufacturing teams. The beauty of cloud-based CAD is that team members can review designs and collaborate in real time via Macs, PCs and mobile phones, rather than the expensive workstations and huge files associated with traditional CAD and computer-aided manufacturing (CAM) systems. Get a copy of this report and discover how manufacturers now have the ability to develop innovative products much faster and far more efficiently than ever before.